Analisis Pelaksanaan Layanan Konseling Individu Melalui Problem Check List dan Catatan Anekdot di SMK Mandiri Tembung - Siregar, Afnita Marni; Harahap, Ade Chita Putri; Ikhsan, Bastothum; Prayetno, Miftah Suhaila; Ramadhan, Muhammad Fiqri; Abdillah, Rizky; Thasfa, Saida Amini (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
School as an educational institution and a means to achieve educational goals. Within the school environment, students are required to adhere to the rules and regulations. The purpose of this research is to determine the individual counseling services in the problem check list and anecdotal records at SMK Mandiri Tembung. This research uses a descriptive qualitative research method. Data collection techniques include observation, interviews, and documentation. The research subjects are the counseling teacher and students in the X class of Light Vehicle Engineering. The results of this study show that the implementation of individual counseling services in the problem check list and anecdotal records at SMK Mandiri Tembung indicates that the counseling teacher has provided individual counseling services to students with individual problems.